2022
DOI: 10.1037/fam0000903
|View full text |Cite
|
Sign up to set email alerts
|

Rules of engagement: A content analysis of accepted and rejected marriage proposals.

Abstract: Little research exists concerning the Western marriage proposal ritual, and rejected proposals are particularly understudied. The current research used the lens of life script theory to quantitatively and qualitatively analyze 374 first-person written accounts of accepted and rejected marriage proposals between men and women that were sampled from online forums. Rejected proposals were more likely than accepted proposals to violate the proposal script. Compared to accepted proposals, rejected proposals include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies of engagement proposals (Chinichian 2008;Hoplock 2016;Hoplock and Stinson 2022;Hunter 2011;Lamont 2014;Moore, Kienzle, and Flood Grady 2015;Ponzetti 2005;Sassler and Miller 2011;Schweingruber, Anahita, and Berns 2004;Sniezek 2013) agree on a number of points, including that the proposal is a ritual with standard elements that ratifies an earlier agreement to marry. This research has identified several standard elements of the proposal (even though they may not be present in every proposal).…”
Section: The Standard Engagement Proposal Scriptmentioning
confidence: 99%
“…Previous studies of engagement proposals (Chinichian 2008;Hoplock 2016;Hoplock and Stinson 2022;Hunter 2011;Lamont 2014;Moore, Kienzle, and Flood Grady 2015;Ponzetti 2005;Sassler and Miller 2011;Schweingruber, Anahita, and Berns 2004;Sniezek 2013) agree on a number of points, including that the proposal is a ritual with standard elements that ratifies an earlier agreement to marry. This research has identified several standard elements of the proposal (even though they may not be present in every proposal).…”
Section: The Standard Engagement Proposal Scriptmentioning
confidence: 99%